Effects of Suaeda rigida extract on the growth performance, antioxidant capacity and immune function of Karakul sheep - Sha, A; Liu, Y; Hao, H (Journal of the Hellenic Veterinary Medical Society, 2024)
The objectives of this study were to investigate the effects of dietary supplementation of Suaeda rigida extract on the growth performance, antioxidant capacity and immune function of Karakul sheep. Blood samples were collected from the jugular veins before morning feeding on the 10th, 20th and 30th days of the trial period, respectively, and the serum antioxidant and immune indexes of Karakul sheep in the control and experimental groups were determined. The results showed that the growth performance of Karakul sheep was dramatically improved by dietary supplementation of Suaeda rigida, the contents of NO, cGMP, MDA, H2O2, •OH and the activities of XOD, GGT, NOS in the serums of Karakul sheep were inhibited to varying degrees, the GSH content and the activities of GSH-Px, GST, CAT and SOD were substantially increased (P<0.05 at 10d, P<0.01 both 20d and 30d). At 30 days, the contents of total protein, globulin, calcium and three immunoglobulins including IgG, IgA, IgM in the sera of experimental Karakul sheep were significantly higher than those in the control group (P<0.05). All the results suggested that the growth performance, antioxidant, anti-aging capacity, immune function, and life extension of Karakul sheep were significantly improved by dietary supplementation with Suaeda rigida.